The Impact of Apple's App Tracking Transparency Framework on the App Ecosystem - Cristobal Cheyre; Benjamin T. Leyden; Sagar Baviskar; Alessandro Acquisti (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study the impact of the implementation of Apple's App Tracking Transparency (ATT) framework on the Apple App Store ecosystem. We use comprehensive data on every app available in both the Apple App Store and Google Play Store ecosystems in the eighteen-month period around the implementation of ATT, and a difference-in-differences analysis to investigate whether the introduction of the privacy transparency framework affected the incentives for developers in the Apple ecosystem to create new apps, update their existing apps, or withdraw from the market. We also leverage data on the presence of Software Development Kits (SDK) in a select number of apps in each ecosystem to study how developers adapted specific functionalities in their products, such as the use of advertising platforms or payment systems. We find that the number of available apps in the Apple App Store ecosystem quickly recovers after an initial drop following the introduction of ATT. When analyzing the use of SDKs, we find a reduction in the use of Monetization and Ad Mediation SDKs, and an increase in the use of Authentication and Payments SDKs. Our results suggest developers did not withdraw from the market after ATT and instead adapted to operate under the conditions of a more protective privacy framework.
Keywords: 330